First report of the predominance of clonal complex 398 Staphylococcus aureus strains in osteomyelitis complicating diabetic foot ulcers: a national French study. (2nd October 2013) - Senneville, E.; Brière, M.; Neut, C.; Messad, N.; Lina, G.; Richard, J.‐L.; Sotto, A.; Lavigne, J.‐P.; ,; Tassios, P.
Abstract Staphylococcus aureus is the most common pathogen cultured from diabetic foot infection including diabetic foot osteomyelitis. This French multicentre study determined the genetic content of S. aureus isolated from 157 consecutive cases admitted to 12 diabetic foot centres between 2008 and 2011. We describe for the first time the emergence of the CC398 methicillin‐susceptible S. aureus clone, the main clone in diabetic foot osteomyelitis, and its tropism for bone. This clone spreads to humans from an animal source through its intrinsic virulence. This adaptation of S. aureus isolates looks to be a worrisome problem and should be carefully monitored.